2011
DOI: 10.1111/j.1464-5491.2011.03329.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of insulin glargine in patients with Type 2 diabetes in suboptimal glycaemic control positively impacts health‐related quality of life. A prospective cohort study in primary care

Abstract: Results of this observational study demonstrate combined glycaemic and health-related quality of life benefits of initiating insulin glargine in patients with Type 2 diabetes in routine primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…Similar results were obtained in a Chinese observational study evaluating the effect of initiation of biphasic insulin aspart 30 in 6,612 insulin naïve patients, or switching to this insulin analogue in 1,966 already insulin-treated subjects [21]. In a Dutch prospective cohort study, initiation of insulin glargine in both insulin-naïve as well as in insulin-treated patients with type 2 diabetes, resulted in improvement in QoL [22]. However, in a prospective, multicentre, randomized, open label, crossover study conducted in Holland, no differences were found between patients initiating insulin glargine and insulin NPH regarding QoL [23].…”
Section: Discussionsupporting
confidence: 66%
“…Similar results were obtained in a Chinese observational study evaluating the effect of initiation of biphasic insulin aspart 30 in 6,612 insulin naïve patients, or switching to this insulin analogue in 1,966 already insulin-treated subjects [21]. In a Dutch prospective cohort study, initiation of insulin glargine in both insulin-naïve as well as in insulin-treated patients with type 2 diabetes, resulted in improvement in QoL [22]. However, in a prospective, multicentre, randomized, open label, crossover study conducted in Holland, no differences were found between patients initiating insulin glargine and insulin NPH regarding QoL [23].…”
Section: Discussionsupporting
confidence: 66%
“…Patients were invited to participate in the SPIRIT and ESPRIT studies by their primary or secondary care treating physician if there was a clinical necessity to initiate long-acting insulin. Both studies are described in more detail elsewhere (14,15). The present analyses used only baseline data collected before insulin initiation or intensification.…”
Section: Methodsmentioning
confidence: 99%
“…The HPR specializes in the development and use of Patient-Reported Outcome measures in diabetes research and have been used in previous studies that accessed TS and QoL. 7,8 A licence agreement before using the questionnaires was obtained by the study sponsor.…”
Section: Assessment Of Diabetes Dependent Quality Of Life and Diabetementioning
confidence: 99%
“…6 Several clinical trials demonstrated efficacy of insulin treatment in insulin-naïve patients and favourable effects on HRQoL. 5,7,8 However, for patients with T2DM starting a long-acting insulin as an add-on treatment on OADs in Greece, data on the effect on QoL indices are limited or poorly documented.…”
Section: Introductionmentioning
confidence: 99%